An investigation into path analysis for line-of-sight microwave radio - Gale, David James (University of Cape Town, 2014)
Includes bibliography. === An investigation into the analysis of Digital Microwave Radio Paths was conducted. The causes and effects of multipath fading on the propagation of microwave signals are of particular interest here. A study is made of the theory of link engineering, including an examination of fading and distortion, and the instrumentation used in the analysis of link performance. Multipath fading, the different categories, as well as the causes and effects thereof, are reviewed. The Tellurometer Method of distance measurement is described and its suitability to path analysis discussed.